BEST PRACTICE INOVASI PELAYANAN PUBLIK KEMBALI UPAYAKAN DUKUNGAN UNTUK SEKOLAH (KUDU SEKOLAH) DALAM MENANGANI ANAK TIDAK SEKOLAH DI KABUPATEN PEKALONGAN - Della Paramitha, Yulia; Marom, Aufarul; Nurcahyanto, Herbasuki (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
KUDU Sekolah is a public service innovation in the education sector which has received the TOP 45 Public Service Innovation award at the SINOVIK 2021 event. KUDU Sekolah aims to reduce the number of Unschooled Children (ATS) in Pekalongan Regency. KUDU Sekolah succeeded in reducing the number of ATS by returning 2,396 children to school from 2019-2023. This research aims to analyze the implementation of the KUDU Sekolahpublic service innovation in Pekalongan Regency in terms of best practice aspects and identify supporting and inhibiting factors in its implementation. This research uses the concept of Best Practice according to Prasojo, namely Impact, Partnership, Sustainability, Leadership, and Transferbility. Meanwhile, the supporting and inhibiting factors use the 5 elements of management theory according to Harrington Emerson, namely Man, Money, Materials, Machine and Methods. The method used in this research is a descriptive qualitative method. Data collection techniques were carried out through interviews and documentation. The research results show that the implementation of the KUDU Sekolah innovation has met all the best practice criteria. Supporting factors for implementing the KUDU Sekolah innovation are the availability of an adequate budget, adequate facilities and infrastructure, the application system is available in two versions (website & android) which makes data collection-monitoring-evaluation easier and can be accessed without the internet, as well as procedures for implementing the KUDU Sekolah innovation that are easy and supported by ATS door to door activities. The inhibiting factor in the implementation of KUDU Sekolah innovation is that there are still Village Level KUDU Sekolah Team who do not master technology and lack discipline.